Smart Grid technology, transmission of electrical energy in power supply and lighting systems of cities - Hovorov, Pylyp Paramonovych; Hovorova, Kateryna Vladlenivna; Kindinova, Anastasiia Kostyantynivna; Abdelrahim, Omer (Національний технічний університет "Харківський політехнічний інститут", 2020)
Modern power supply and lighting systems of cities are complex electrical systems of an automated type, in which the processesin individual power supply systems and city lighting systems are interconnected andinterdependent. Therefore, the search for efficient technologies for the transmission of electrical energy in them is an extremely difficult task. The real state of the power supply and lighting systems in cities today is characterized by low operating efficiency, largely due to the low quality of electrical energy and insufficient compensation of reactive power in them. The mutual influence of power supply and lighting systems in cities, as well as the presence of significant voltage deviations and the overflow of additional reactive power in the networks, causes an increase in voltage and power losses inthem, as well as a decrease in the efficiency of networks and connected consumers, in general. Unfortunately, the existing methods and technical means based on them cannot fully solve this problem. The research carried out made it possible to clarify the nature of the processes in the power supply systems and the sanitation of cities and to determine the methods and technical means based on the Smart Grid concept. They are based on the use of phase-shifting booster transformers with an electronic control system. Their use made it possible to provide the possibility of complex control of the voltage modes of active and reactive power with the possibility of installation at any point in the network and centralized control from a single centre. The calculations show that the use of the developed methods and technical means provides an opportunity to reduce power losses in networks by 10–15% and energy costs for consumers by 50–75%.

Сучасні системи електропостачаннята освітлення міст являють собою складні електротехнічні системи автоматизованого типу, в яких процеси в окремо взятих системах електропостачання та системах освітлення міст є взаємопов’язаними та взаємозалежними. Тому пошук ефективних технологій передавання електричної енергії в них є задачею надзвичайної складності. Реальний стан систем електропостачання та освітлення міст сьогодні характеризується низькою ефективністю роботи, що в значній мірі пов'язано з низькою якістю електричної енергії та недостатньою компенсацією реактивної потужності в них. Взаємний вплив систем електропостачання та освітлення міст, а також наявність значних відхилень напруги і перетікання додаткової кількості реактивної потужності в мережах обумовлює підвищення втрат напруги і потужності в них, а також зниження ефективності роботи мереж і підключених споживачів, в цілому. На жаль, існуючі методи і технічні засоби, засновані на них, не можуть вирішити цю проблему в повній мірі. Проведені дослідження дозволили уточнити характер процесів в системах електропостачання та освітлення міст і визначити методиі технічні засоби, засновані на концепції Smart Grid. В їх основу покладено застосування фазоперемикаємих вольтододавальних трансформаторів з електронною системою управління. Їх застосування дозволило забезпечити можливість комплексного управління режимами напругиактивної і реактивної потужності з можливістю установки в будь-якій точці мережі і централізованим управлінням з єдиного центру. Проведені розрахунки свідчать про те, що застосування розробленихметодів і технічних засобів надає можливість зменшення втрат потужності вмережах на 10-15% і витрати енергії у споживачів 50-75%.
Smart Grid технології, передача електричної енергії в системах електропостачання та освітлення міст
Keywords: efficiency; electrical energy; ефективність; електрична енергія